PENURUNAN KADAR Fe DENGAN MEMBRAN KERAMIK PADA AIR SUMUR (Studi Kasus Pada Wilayah Kerja Puskesmas Putat Jaya Tahun 2018) - Anggit Prameitya; Darjati .; Ernita Sari (GEMA LINGKUNGAN KESEHATAN, 2018)
Water is the element of life that is essential for survival. Along with the rapid growth of the human being, the demand for water increases. Now this, many water sources are contaminated, clean one of the impacts that cause pollution is that there is content of Fe in the water. Fe is the secondary contaminants that become problems in the provision of clean water is especially groundwater. The content of Fe exceeds quality raw processing must be done first before used to clean water. This research aims to analyze Fe levels before and after filtration is done using ceramic membrane media with a thickness of 5 cm and 7 cm in well water.This research is experimental research, using design research True Experiment with form One Group Pretest-Posttest. The object of this research that is well water containing Fe levels with a total of 32 Research sample sample. Further data obtained were analyzed using analytical test in Paired-Samples T Test.The results showed that the ceramic membrane filter media thickness 5 cm and 7 cm is capable of lowering the average rate of 8.11 Fe mg/l be 5.9 mg/l and 3.6 mg/l. The results of statistical tests using Paired T-test Test earned the result that there is a difference Fe levels before and after treatment using ceramic membrane filter media with variations in the thickness of 5 cm and 7 cm.The conclusion of this research is the ceramic membrane thickness 7 cm has the difference decreased most in lowering levels of Fe on well water. It is recommended to increase the creativity in applying appropriate technology in filtration method. Keywords: water well, levels of Fe, ceramic membranes